Legal Study on Overclaims on Food Products in the Perspective of Consumer Protection Law - Arya Wira Prabaswara (Eduvest - Journal of Universal Studies, 2025)
One of the consumer rights is to get correct information, this is also regulated in Law Number 8 of 1999 concerning Consumer Protection, known as UUPK, however, in reality, violations of consumer rights often occur, including food products containing overclaims that can harm consumers themselves, therefore the purpose of this study is to find out how the law protects consumer interests.